THE CHARACTERISTICS OF NASOPHARYNGEAL CARCINOMA PATIENTS IN MOEHAMMAD HOESIN GENERAL HOSPITAL PALEMBANG JANUARY 2013 - DECEMBER 2017 - Denny Satria Utama (TALENTA PUBLISHER, 2019)
Introduction Nasopharyngeal carcinoma is a malignant tumor that grows in nasopharyngeal area with a predilection in fossa of Rossenmuller and roof of nasopharynx. Nasopharyngeal carcinoma is the most common malignant tumor in the neck and head area. This research is to determine the characteristics of nasopharyngeal carcinoma at Moehammad Hoesin General Hospital Palembang. Methods This study design is restrospective descriptive and took the sample from medical records in department of ORL-HNS Moehammad Hoesin General Hospital Palembang between January 2013 until December 2017. Results In this study, the number of nasopharyngeal carcinoma patients January 2013 to December 2017 was 284 patient. Most of them were male (72.86%). The age of most patients ranges from 41-50 years (33.20%). The highest histopathological description of patients was WHO 2B (54.9%). Most patients were T4 (36.29%). Most patients nodules were N3 (34.09%). As many as 93.88% of patients have not experienced distant metastasis. Most patients came to the department of ORL-HNS had already been in stage IV (63.84%). The most chemotherapy regimens given were carboplatin and docetaxel. Conclusions Nasopharyngeal carcinoma is still a problem in many countries. The main management is radiotherapy with or without chemotherapy.